2014
DOI: 10.14355/ijap.2014.0302.05
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Product Design and Perceived Brand Emotion

Abstract: Product aesthetics give people a sense of beauty and impression and encourages them to consume and collect. Companies employ shapes that are both emotionally appealing and compatible with the brand's image of aesthetics in generating favorable consumer responses. Existing research on branding and product design has demonstrated the importance of emotions. Consumers can base their evaluations of a brand extension on their subjective-affective reactions toward products. Many products are designed to attract cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…• Commerce, Brand Management, Customer Relationship Management, and FinTech (Finance and Technology): Sentiment analysis of blogs, tweets, and Facebook posts is already widely used to shape brand image, track customer response, and in developing automatic dialogue systems for handling customer queries and complaints (Ren & Quan, 2012;Yen, Lin, & Lin, 2014).…”
Section: Applicationsmentioning
confidence: 99%
“…• Commerce, Brand Management, Customer Relationship Management, and FinTech (Finance and Technology): Sentiment analysis of blogs, tweets, and Facebook posts is already widely used to shape brand image, track customer response, and in developing automatic dialogue systems for handling customer queries and complaints (Ren & Quan, 2012;Yen, Lin, & Lin, 2014).…”
Section: Applicationsmentioning
confidence: 99%
“…explanation, and criticism, to understand the change surrounding the life by explaining statistical charts, and to precede reasonable predictions of uncertain situations (Yen et al, 2014).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…At the evaluation stage, when consumers completed search and acquired enough information, they would evaluate the optimal choices and make decisions. The evaluation standard was the expected result from the viewpoints of consumption and purchase to further present on the preferred product attributes (Yen et al, 2014). In other words, Chien et al (2015) indicated that the data search and evaluation stage required the match between product designers and consumers; product designers had to perceive consumers' preference and needs for product attributes so as to design consumers' favored products and enhance consumers' purchase intention to be willing to purchase such products (Chowdhury et al, 2014).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…Verganti [4] pointed out that the meaning of a product comes from the interaction between the user and the product. Lin Rongtai [5][6][7] argues that cultural and creative products use cultural elements as a source of originality to meet the needs of users' spiritual dimension. Therefore, in addition to cultural elements, China's cultural and creative product design should also integrate emotions into the design so that the product can be identified with different cultural groups around the world while its ethnicity is being maintained [8].…”
Section: Introductionmentioning
confidence: 99%